My Best Book of Creepy Crawlies - Llewellyn, Claire; Illustrated by Forsey, Chris & Andrea (London King Fisher, 1998)
Introduces a variety of insects and spiders, describing their physical characteristics, habitats and life cycles
Include Colors Illustration, Glossary and Index
Keywords: Arthropoda